Visual framing of Islam in online newspapers: evidence from selected Muslim-majority nations - Isyaku, Hassan; Mohd Nazri, Latiff Azmi (2020)
Purpose of the study: This study comparatively explores Islam-related visual elements in selected online newspapers from Nigeria and Malaysia. Methodology: A total of 425 photos and 23 videos published alongside Islam-related news collected from selected online newspapers between November 2015 and September 2016 were analyzed via content analysis. Main Findings: The findings reveal that 43 out of the total number of photos reproduced violence while no violent videos were found in the select newspapers. It was also found that some of the photos used in the selected newspapers were either unrelated to the event being reported or used in different reports. Applications: This study could be valuable for practicing journalists in the process of carrying out their jobs. It is also intended to influence the newspaper management decisions on how to disseminate information that is free of bias and maintain accountability for their news. Novelty/Originality: This study provided evidence on the visual framing of Islam in online newspapers, particularly within Muslim-majority states.